Factors affecting the adoption and use of gene expression profiling by oncologists in clinical practice. (January 2015) - Patil, Dhaval; Issa, Amalia M
Aim: In this study, we evaluated the association between oncologists' perceptions of and attitudes toward one frequently used gene expression profiling assays, the Oncotype DX ® and oncologists' intention to use this assay in making treatment recommendations for breast cancer patients.Methods : A nationally representative sample of breast cancer oncologists was surveyed using an adapted technology acceptance model.Results : The survey response rate was 44.1%. The test characteristics `validity of the test' (p = 0.006) and 'use of Oncotype DX by fellow oncologists' (p = 0.0068) were significantly associated with use of the assay by oncologists. Oncologists' intention to use Oncotype DX increased consistently with their perceptions about its usefulness (β = 0.222). Insurance status of the patients was also significantly associated with physicians' use of Oncotype DX (p = 0.008).Conclusion : We report a novel application of an adapted technology acceptance model to understand the adoption of gene expression profiling by oncologists who treat breast cancer patients in making treatment recommendations.